Teaching performance and professional training at the UPT Professional School of Accounting and Financial Sciences, 2014 - Peñaloza Arana, Eloyna Lucia (2015)
Objective: This research was  conducted in order to establish the  influence of Teaching Performance  in the formation of Professional  Accountants in the Professional  School of Accounting and Finance of  the Private University of Tacna, in  2014. Method: The research was carried  out basic research, whose design is  the relational descriptive. For this  purpose the information obtained  through the application of the  measurement instument of the  questionnaire for assessing teacher  performance and training of  Professional Accountants, which  were applied to graduates and  students of the last cycle, the survey  technique was considered , using a  Likert scale. Results: After the phase of analysis  and interpretation of results  established that there is a significant  relationship between teacher  performance and training of  Professional Accountants in the  Professional School of Accounting  and Financeof the Private University  of Tacna, in 2014. Conclusions: Teachers of the  Professional School of Accounting  and Finance of the Private University  of Tacna have a regular teacher  performance level; and the formation  of Professional Accountants in the  Professional School of Accounting  and Finance of the Private University of Tacna is acceptable